Pemeriksaan ANC Gratis Dan Penyuluhan Pada Ibu Hamil Di Desa Sukarahayu - Ikha Prastiwi; Marini Iskandar; Dewi Agustin; Ade Krisna Ginting; Rifka Alindawat; Rizky Fitri Andini; Kartika; Neng Revhi; Nengsih Yulia (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
Background: Based on data from the World Health Organization (WHO) in 2011 as many as 536,000 women died due to childbirth. As many as 99% of maternal and infant deaths due to labor or birth problems occur in developing countries, while the maternal mortality rate (MMR) and infant mortality rate (IMR) in 2011 were 81% due to pregnancy complications, pregnancy complications due to low maternal visits. pregnant (Antenatal Care) so that these complications are not detected early. Purpose: motivates to carry out routine ANC checks to health services at least 4 times during pregnancy Method: The activity was carried out by the team, by carrying out the assigned tasks, at table 1 namely registration, table 2 checking blood pressure, height and weight, table 3 assessment, table 4 physical examination then laboratory examination and ended with counseling. Results: The result of community service is the achievement of ANC examinations for pregnant women and counseling about pregnancy. The results are in accordance with the target, which is 100% pregnant women carry out ANC checks and counseling Conclusion: the community gave a positive response so that the activity had reached the target, namely out of 16 pregnant women identified in Sukarahayu Village, 100% had carried out ANC checks